Inside-Outside Circle Instructional Model For Multicultural Education - Akhiruddin Akhiruddin; Sukmawati Sukmawati; Jalal Jalal; Sujarwo Sujarwo; Ridwan Ridwan (Universitas Pendidikan Ganesha, 2021)
Indonesia is one of the largest multicultural countries in the world. This reality can be seen through the diverse and extensive socio-cultural and geographical conditions. This study aims to investigate the implementation of the Inside-Outside Circle (IOC) instructional model for the multicultural education. This research used qualitative and quantitative methods. Methods of data collection using observation, interviews and literature study. The results showed that multicultural education can be used as a strategic instrument to develop awareness of one's pride in one's ethnic group. Multicultural education is also very relevant to a pluralistic society such as Indonesia, which emphasizes an understanding of multi-ethnicity, multi-religion, and multiculturalism which requires a new construction of justice, equality and a democratic society. The application of integrative multicultural education can use a cooperative learning model, namely the Inside-Outside Circle (IOC) linstructional model and the application of multicultural education in an integrated curriculum with other subjects such as in the Sociology Education program.